Suppression of acute and chronic mesial temporal epilepsy by contralateral sensing and closed-loop optogenetic stimulation with proportional-plus-off control. (May 2019) - Lin, Bing-Hong; Ju, Ming-Shaung; Lin, Chou-Ching K.
Highlights: A novel control of optogenetic stimulation to suppress seizure was developed. A combination of frequency band and signal complexity of electrical activity was used to detect seizures. Seizure detection was performed on the side contralateral to the side of optogenetic stimulation. The control system worked well for both acute and chronic stages of seizures. The system can be an energy-saving solution opposed to the open-loop continuous stimulation. Abstract: A proportional-plus-off control of optogenetic stimulation is implemented using the sample entropy and frequency bands of contralateral depth EEG as the afferent signals for seizure detection and feedback control. The system is tested on mice with mesial temporal epilepsy, induced by lithium-pilocarpine injections. The hippocampus is photic stimulated through an optical fibre inserted using the stereotactic technique, and depth EEG from the hippocampus contralateral to the photic-stimulation site is used to calculate the sample entropy and frequency bands, which, in turn, are utilized to classify the types of seizures. According to a lookup table, the proportional-plus-off controller maps the SEn to the control signal and regulates the intensity of the photic stimulation to the hippocampus. The average rates of correct seizure detection are >90% in both acute and chronic stages. The average rates of successful seizure suppression are 86–98% in the acute stage and 94.3% in the chronic stage. The results indicate that the contralateral sensing and closed-loop proportional-plus-off control of optogenetic stimulation is feasible for seizure control.